Customer Service Orientation and Organizational Citizenship Behavior: Insights from Civil Servants and Corporate Employees - Bakar, Resekiani Mas; Burhanuddin, arinil Hidayah; Lukman, Lukman; Syam, Rahmawaty (Jurnal Psikologi TALENTA, 2025)
This study offers a novel contribution by exploring the role of customer service orientation in enhancing organizational citizenship behavior (OCB) through a comparative analysis between civil servants and private sector employees. The objective is to address a gap in existing literature concerning the differential effects of extra-role behaviors on service delivery across these sectors. The research also explores how customer service orientation influences OCB. Data were collected from 346 employees, comprising public-sector civil servants and their private-sector counterparts, utilizing the customer service orientation and organizational citizenship behavior scales as the primary measurement instruments. Findings reveal that customer service orientation significantly predicts OCB. Notably, while the conscientiousness dimension of OCB shows no significant difference between civil servants and private sector employees, overall OCB and customer service orientation exhibit distinct patterns between the two groups. In particular, private sector employees demonstrate a higher propensity towards extra-role behaviors closely linked to enhanced service delivery. Conversely, for optimal service provision in the public sector, civil servants must adopt and internalize the principles of BerAKHLAK, with a specific emphasis on service orientation. This study underscores the role of organizational citizenship behaviors in defining service quality across public and private sectors.